2013
DOI: 10.1016/j.annals.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity and the Pseudo-Backstage of Agri-Tourism

Abstract: This article explores how summer farmers in Bregenzerwald (Austria) and Valdres (Norway) deal with their double role as farmers and tourist hosts. Based on qualitative interviews with farmers, the authors discuss how this double role influences tourist-host interactions and the staging of summer farms, and the ways in which the discourses of authenticity and heritage manifest themselves therein. In both Austria and Norway, summer farms are objects of idyllisation. They are highly suitable places for agri-touri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 28 publications
(33 reference statements)
1
49
1
2
Order By: Relevance
“…Wang (1999) argues that existential authenticity stems from the visitor's lived experience; including physical feelings and self-making (Mura, 2015). Existentially authentic experiences are not simply about visiting sites of socially constructed significance, but participating and experiencing something fulfilling, engaging, and fundamentally dissimilar to the normality of everyday life (Daugstad and Kirchengast, 2013). Reisinger and Steiner (2006) and Kolar and Žabkar (2010) found that both existential and object-based authenticity were related to cultural motivation, while Bryce et al (2015) suggest that cultural motivation positively influences existential authenticity.…”
Section: Host Sincerity and Related Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang (1999) argues that existential authenticity stems from the visitor's lived experience; including physical feelings and self-making (Mura, 2015). Existentially authentic experiences are not simply about visiting sites of socially constructed significance, but participating and experiencing something fulfilling, engaging, and fundamentally dissimilar to the normality of everyday life (Daugstad and Kirchengast, 2013). Reisinger and Steiner (2006) and Kolar and Žabkar (2010) found that both existential and object-based authenticity were related to cultural motivation, while Bryce et al (2015) suggest that cultural motivation positively influences existential authenticity.…”
Section: Host Sincerity and Related Conceptsmentioning
confidence: 99%
“…While existential in nature, tourists' sincere emotional response is not necessarily concerned with fulfilment and engagement (Daugstad and Kirchengast, 2013), nor intrapersonal feelings generated from attachment to the destination or objects therein (Bryce et al, 2017). It does not simply acknowledge that interactions occur (Yi et al, 2017), but focuses on the emotional responses elicited within the tourist as an outcome of these interactions.…”
Section: [Table 1]mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the popularity of this stream of research, Poria, Reichel and Biran (2006) point out little research focuses on how tourists perceive heritage attractions and what they expect from them (Poria, Butler, and Airey 2004 (Ahmad 2006;Daugstad and Kirchengast 2013). While the latter taps more into the natural aspect of heritage (e.g.…”
Section: The Impact Of Company Involvement In the Restoration Of Herimentioning
confidence: 99%
“…This practise is important for farmers because it supplements the annual forage budget, allows access to public subsidies (Mack et al 2013;Zendri et al 2013;Battaglini et al 2014), and can increase revenue through processing of the milk into high-value traditional cheeses (Sturaro et al 2013a). In addition, the cultural landscape of the summer farms provides positive externalities by increasing local tourist attractiveness (Thiene & Scarpa 2008;Daugstad & Kirchengast 2013), maintaining cultural heritage and traditions (Baudry & Thenail 2004;Kianicka et al 2010;Eriksson 2011), supporting the biodiversity of farmed livestock (Sturaro et al 2013a) and conserving natural habitats and species of high conservation value (Marini et al 2011).…”
Section: Introductionmentioning
confidence: 99%